PERANCANGAN MESIN PEMILIHAN BUAH TOMAT MENGGUNAKAN MIKROKONTROLER BERBASIS TCS230 - Basri, Muhammad Hasan; Akbar, Saiful (POLITALA PRESS, 2025)
This research is about post-harvest tomato selection where the TCS230 color sensor Will go through a way of assessing light intensity by emitting caused by super bright leds through objects, reading light intensity values ​​starting with an 8x8 photodiode matrix, on 64 photodiodes will be divided into 4 parts of color reading, on the color illuminated by the led reflected by the led light to the photodiode, the reflection of the light will be extended by a wave that changes depending on the color of the object being detected, the TCS230 color sensor can read several colors. A tomato will enter its place, the tomato may always stop right under the sensor so that the sensor will not be able to detect the presence of tomatoes that pass, and cannot read the RGB value of the tomatoes that pass. The results of 10 tests showed that selecting tomatoes successfully classified tomato grades, could control servo motors and DC motors automatically based on RGB values ​​through a processing time of about 3 seconds with an error rate of 2%.